Effects of class size reduction in upper grades: Evidence from Seoul, Korea. (October 2017) - Han, Joseph; Ryu, Keunkwan
Abstract: We study the effects of class size reduction (CSR) in upper grades (10–12) on college entrance exam scores, using merged Korean administrative data. This data set provides a rare opportunity to investigate the effects of high school class sizes on student outcomes. Seoul has maintained strong restrictions on educational choices to achieve the ideal of equal educational opportunities. The identification mainly comes from the large-scale CSR policy implemented in 2002. By using the within-school between-cohort variation in class size intended by the CSR policy, we find that the effects of high school class sizes on test scores are small with tight confidence intervals. We confirm this result by using the additional within-school variation in class size arising from the major division, especially the implicit rule of class allocation between majors. Further, the distributional effects are no different from the average effects either.